The vertical structure and variability of currents east of Philippines from mooring measurements during the 2015/2016 El Niño - Liu, Yansong; Ren, Qiang; Yu, Fei; Wei, Chuanjie; Diao, Xinyuan; Nan, Feng (Frontiers in Marine Science, 2023)
Surface and Subsurface currents in the Philippine Sea have been reported previously, and the debate persists regarding whether they are related to the strength of ENSO (El Niño/Southern Oscillation). We investigated the mean vertical structure and variability of the currents along the western boundary of the Philippine Sea using mooring observations at about 8°N, 127°E from August 2014 to January 2016. The southward Mindanao Current (MC) exists in the upper 600 m countered by the northward Mindanao Undercurrent (MUC) observed below 600 m to the depth of 2,000 m, with a core at approximately 1,000 m. During the development of El Niño from July to December 2015, the core velocity and depth of the MC were noticeably increased, consistent with the Niño 3.4 index, and the current at 2,000 m was observed to be southward, which indicated that the MC may extend to 2,000 m under the influence of El Niño. The MUC was stronger around November 2015, corresponding to the peak phase of the Niño 3.4 index. The intraseasonal variability with a period of 70-110 days from the surface to 2,000 m is also discussed based on power spectral analysis. Subsurface eddies are likely the source of the intraseasonal variability of current in the Philippine Sea from the model outputs.